Competitive solutions : the strategist's toolkit - McAfee, R. Preston (Princeton University Press, 2002)
"This book is an examination of modern business strategy and its application in many different settings. Students of business and economics - as well as executives and managers - will recognize Competitive Solutions as an indispensable resource as well as a definitive vision of the strategic firm: one in which each element of company strategy reinforces the other elements."--Jacket.